2022
DOI: 10.1021/acsanm.2c04268
|View full text |Cite
|
Sign up to set email alerts
|

Core–Shell Nanostructures of Tungsten Oxide and Hydrogen Titanate for H2 Gas Adsorption

Abstract: Nanostructured tungsten oxide is a promising material for sensing reducing gases such as hydrogen. However, this material exhibits limitations due to a poor response toward sensing at room temperature, incomplete recovery to the initial state, long response time, and a low response factor, which is not desired for explosive gases like hydrogen. In this work, we, for the first time, demonstrate that these limitations can be significantly overcome using the core–shell structure of tungsten oxide (WO3) nanorods a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 82 publications
0
7
0
Order By: Relevance
“…It is evident that a greater number of oxygen atoms is sputtered out from the nanorod surface because of preferential sputtering due to higher stoichiometry ratio and the lower atomic mass of oxygen compared with iron. 17,19 The TRI3DYN simulations also confirmed the ion beam mixing, which is much more prominent at the junction point and plays a crucial role in the formation of welded homo-junctions between the hematite nanorods.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…It is evident that a greater number of oxygen atoms is sputtered out from the nanorod surface because of preferential sputtering due to higher stoichiometry ratio and the lower atomic mass of oxygen compared with iron. 17,19 The TRI3DYN simulations also confirmed the ion beam mixing, which is much more prominent at the junction point and plays a crucial role in the formation of welded homo-junctions between the hematite nanorods.…”
Section: Resultsmentioning
confidence: 69%
“…Ar + ions were chosen because of their inertness and the higher capacity for creating cascade-collision-induced defect states because of their higher atomic mass. Previous studies on Ar + ion irradiation have shown remarkable enhancements in properties, such as gas sensing, 16 optical detection, 17 energy storage, 18 hydrogen adsorbtion, 19 nano-device fabrication 20,21 etc., owing to changes in the surface defects and morphological modifications. 22,23 Other important aspects of 1D hematite are its application in sensing, catalysis, and energy devices.…”
Section: Introductionmentioning
confidence: 99%
“…In this static gas sensing system, sensing data were obtained by measuring resistance using a two-probe method. The sensing unit has a 250 CC testing chamber, where heating-cum-mounting platform of the samples, electrodes to connect Keithley probes, gas inlet, and outlets are housed . The ammonia detection technique relies on gas adsorption and desorption processes on the surface of the sensing material.…”
Section: Methodsmentioning
confidence: 99%
“…The sensing unit has a 250 CC testing chamber, where heating-cum-mounting platform of the samples, electrodes to connect Keithley probes, gas inlet, and outlets are housed. 29 The ammonia detection technique relies on gas adsorption and desorption processes on the surface of the sensing material. The sensor was placed in this sealed small chamber at room temperature (25 ± 2 °C) and relative humidity (RH) (50 ± 5%).…”
Section: ■ Experimental Detailsmentioning
confidence: 99%
“…Its bandgap is between 1.2 and 1.8 eV. 18,19 The heterostructures of MoS 2 /MXene nanocomposites renowned for their tunable bandgaps hold great potential in the elds of catalysis [20][21][22] and ion batteries. 23,24 The highly accessible surface and excellent electron-conducting properties of MoS 2 make it promising for efficient NH 3 detection at RT.…”
Section: Introductionmentioning
confidence: 99%